Intellectual disability and borderline intellectual ability: keys for a better labour market insertion - Mariola Serrano Argüeso (Oñati Socio-Legal Series)
People with intellectual disabilities and people with borderline intellectual abilities have high poverty rates and greater difficulties in joining the workforce than the rest of the collective of people with disabilities. The need for their inclusion in the labour market is not only translated into economic terms but also into the improvement of other aspects such as identity and self-esteem. Nowadays, neither collective bargaining nor the business culture through the Corporate Social Responsibility has considered as a priority the treatment of the diversity presented by disabled workers, and even less with intellectual disabilities. This article will analyse the challenges and difficulties that both, people with intellectual disabilities and people with borderline intellectual abilities, have to face in order to take a step forward into the desired full integration into the labour market, and will make some political and legislative proposals to try to alleviate and minimize the current situation.